Efflux pump-mediated resistance to antifungal compounds can be prevented by conjugation with triphenylphosphonium cation. Issue 1 (December 2018) - Chang, Wenqiang; Liu, Jun; Zhang, Ming; Shi, Hongzhuo; Zheng, Sha; Jin, Xueyang; Gao, Yanhui; Wang, Shuqi; Ji, Aiguo; Lou, Hongxiang
Abstract Antifungal resistance due to upregulation of efflux pumps is prevalent in clinicalCandida isolates. Potential efflux pump substrates (PEPSs), which are active against strains deficient in efflux pumps but inactive against wild-type strains, are usually missed in routine antifungal screening. Here we present a method for identification of PEPSs, and show that conjugation with mitochondria-targeting triphenylphosphonium cation (TPP+ ) can enhance or restore the compounds' antifungal activity. The screening method involves co-culturing a wild-typeC. albicans strain and a Cdr efflux pump-deficient strain, labelled with different fluorescent proteins. We identify several PEPSs from a library of natural terpenes, and restore their antifungal activity against wild-type and azole-resistantC. albicans by conjugation with TPP+ . The most active conjugate (IS-2-Pi-TPP) killsC. albicans cells, prevents biofilm formation and eliminates preformed biofilms, without inducing significant resistance. The antifungal activity is accompanied by mitochondrial dysfunction and increased levels of intracellular reactive oxygen species. In addition, IS-2-Pi-TPP is effective againstC. albicans in a mouse model of skin infection. Antifungal resistance due to upregulation of efflux pumps is common inCandida albicans . Here, the authors show that conjugation with mitochondria-targeting triphenylphosphonium cation can enhance or restore the antifungal activity of potential efflux pump substrates.